2011
DOI: 10.1182/blood-2010-10-311415
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA expression signature of osteoclastogenesis

Abstract: IntroductionThe osteoclast, the exclusive bone resorptive cell, is derived from hematopoietic stem cells through the common myeloid progenitor to the colony-forming unit for granulocytes and macrophages to the colony-forming unit for macrophages and into the osteoclast lineage. 1 Osteoclast differentiation, function, and survival are regulated by several exogenous cytokines (macrophage colonystimulating factor [M-CSF], receptor activator of nuclear factor B ligand [RANKL], tumor necrosis factor ␣, interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
253
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(268 citation statements)
references
References 43 publications
9
253
0
1
Order By: Relevance
“…(64) Other miRNAs, such as miR-21 and miR-378, have been implicated in osteoclastogenesis. (65) In particular, miR-21 is of interest because miR-21 is not only known as "inflamma-miR," (66) but has been shown to mediate RANKL-induced osteoclast differentiation (67) and inhibit osteoclast apoptosis. (68) Given that we found significantly higher serum miR-21 serum levels in DMFx than in DM subjects and that DMFx were described to have more cortical porosity, (29) osteoclast dysfunction/or prolonged osteoclast survival might be a potential mechanisms that could explain the higher fracture risk in the DMFx patients.…”
Section: Discussionmentioning
confidence: 99%
“…(64) Other miRNAs, such as miR-21 and miR-378, have been implicated in osteoclastogenesis. (65) In particular, miR-21 is of interest because miR-21 is not only known as "inflamma-miR," (66) but has been shown to mediate RANKL-induced osteoclast differentiation (67) and inhibit osteoclast apoptosis. (68) Given that we found significantly higher serum miR-21 serum levels in DMFx than in DM subjects and that DMFx were described to have more cortical porosity, (29) osteoclast dysfunction/or prolonged osteoclast survival might be a potential mechanisms that could explain the higher fracture risk in the DMFx patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Cultured bone marrow from these mice was incapable of producing osteoclasts ex vivo, further confirming the defect in osteoclast maturation. 8,9 Importantly, this defect was not confined to Dicer; knockdown of DGCR8 and Ago2 using siRNA similarly resulted in decreased osteoclast differentiation and bone resorption, and osteoclastspecific DGCR8 knockout mice display impaired bone development. 7,10 Taken together, these results reveal the necessity for proper miRNA regulation during the differentiation and maintenance of multiple essential cell types required for bone homeostasis.…”
Section: Mirna Regulation Within Bone Marrow Cellsmentioning
confidence: 99%
“…(5)(6)(7)(8)(9) miR-21 regulates osteoclastogenesis of bone marrow-derived monocyte/macrophage precursors (BMMs) via targeting programmed cell death protein 4 (PDCD4). (5) miR-223 expresses in the RAW264.7 osteoclast precursor cell line and controls osteoclast differentiation by regulating nuclear factor I-A (NFI-A) and the macrophage colony-stimulating factor receptor (M-CSFR) levels. (6) In contrast, Mann and colleagues (7) found that miR-155 was downregulated in osteoclasts and upregulated in macrophages.…”
Section: Introductionmentioning
confidence: 99%